Syed Muhammad Naquib al-Attas’ Exposition on the Concept of Ethics - Hidayatullah, Elit Ave; Arif , Syamsuddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Syed Muhammad Naquib al-Attas, is a prominent Malay thinker who has promoted Islamization of present-day knowledge as a solution for the dilemma of Muslims. With that, he has also developed his original thought in various fields. His thought in the field of ethics, the content of adab, the central concept in his system of thought, and the essential teaching of Islam, is hardly elaborated. Thanks to that, it seems crucial to look into his view on ethical norms – its basis and principles – in such a way that his Islamization of ethics by means of infusing worldview of Islam into universal concept of ethics – a concept whose definition is universal, because its element can be found in any specific definition belonging to any worldview – can be known subsequently. Theory of Islamization of present-day knowledge – isolation and infusion process – is used for analyzing al-Attas’ view on ethical norms and theory of transparent worldview is applied also for analyzing his Islamization of ethics. Finally, according to al-Attas, the basis of ethics is religion approved by sound reason, knowledge, and the freedom of the will, whereas its principles are self-perfection, freedom, true faith and knowledge, happiness, and individual contract. As for his Islamized concept of ethics, it is a permanent attitude, action, assertion, and consideration belonging to spiritual aspect of man in his relation to his self, God, society, and state.